The factor of acceptance of shariah compliant in unit trust fund / Azrinnuraisa Samtusi - Samtusi, Azrinnuraisa (2016)
Unit trust is one of the medium of saving and investment for the people who wish to growth their capital in the future. Basically unit trust is pool of funds from many investors who have the same objective to get the capital appreciation and dividend. There are 39 of unit trust companies that run the same concept of investment business in Malaysia. One of the companies of unit trust in Malaysia is Public Mutual Berhad that is wholly-owned subsidiary of Public Bank. Their status as no 1 private unit trust company in Malaysia giving them an advantage as customers who will aware about their products as they conquered the market share compare to the other 38 competitors. So, this study is conducted to know the factors of acceptance of shariah compliant in unit trust fund. This study will identify the customers perception and opinion about the shariah unit trust investment based on potential investors, new investors and unit trust consultant. Primary data such as interviews and observation has been used to collect the internal data. Secondary data like journals, magazines, newspaper and websites are used in order to support the information collected from someone.